A comparison between two Pd‐Ni catalysts supported on two different supports toward Suzuki‐Miyaura coupling reaction. (25th March 2018) - Taheri, Masoud; Ghiaci, Mehran; Shchukarev, Andrey
Abstract : When a single metal fails to promote an efficient Suzuki‐Miyaura coupling reaction at ambient temperature, the synergistic cooperation of two distinct metals might improve the reaction. To examine the synergistic effect of palladium and nickel for catalyzing Suzuki coupling reaction, g‐C3 N4 supported metal nanoparticles of PdO, NiO and Pd‐PdO‐NiO were prepared, characterized and their catalytic activities evaluated over different aryl halides at room temperature and 78 °C. The morphological characterization of Pd‐PdO‐NiO/g‐C3 N4 demonstrated that the bimetallic particles were uniformly dispersed over the g‐C3 N4 layers with diameters ranging from 3.5‐7.7 nm. XPS analysis showed that nanoparticles of Pd‐PdO‐NiO consisted of Pd(II), Pd(0) and Ni(II) sites. The experiments performed on the catalytic activity of Pd‐PdO‐NiO/g‐C3 N4 showed that the prepared catalyst demonstrated an efficient activity without using toxic solvents. Abstract : Pd‐PdO‐NiO/g‐C3 N4 was synthesized as a heterogeneous catalyst for Suzuki coupling reaction and the synergetic effect of the palladium and nickel was investigated.